(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2025)
This study aims to identify the key determinants influencing liquidity risk in both commercial and Islamic banks operating in Saudi Arabia. It further evaluates the comparative performance of these two banking models within the Saudi financial sector. The sample consists of eight banks—four commercial and four Islamic—analyzed over the period 2020–2024 using secondary data extracted from publicly available financial statements. The study examines the impact of firm size, liquidity coverage ratio (LCR), return on equity (ROE), capital adequacy ratio (CAR), and return on assets (ROA) on liquidity risk management. The empirical results reveal a limited yet positive relationship between liquidity risk management and financial performance, particularly when measured through ROE. Moreover, the findings indicate no statistically significant difference in liquidity risk behavior between Islamic and conventional banks, reflecting a convergence of liquidity management practices under the unified regulatory framework enforced by Saudi monetary authorities. Overall, the results provide robust evidence that effective liquidity management contributes to financial stability and enhances shareholder value, though its impact varies according to institutional structure and market conditions.